Considering Authority and Authorship in Technological Contexts in a Brazilian School (LEARNing Landscapes, 2018)
In this narrative inquiry, we inquired into the experiences of Everton and Lowise, two grade 6 English as a Foreign Language students in Brazil, using digital technologies and authoring their texts, in English. In the areas of Applied Linguistics and Education, we consider discussions about the writing process in English and the possibilities of working with genres to teach and learn English through digital technologies. The research participants lived and told stories of freedom, singularity, and responsibility, becoming authors when they left their signature on the professional knowledge landscape of school.
Keywords: stories of authorship; digital technologies; English teaching and learning; narrative inquiry